Unlocking Creative Economic Development and Halal Tourism Through the Wisdom of Tepo Seliro - Aniq Akhmad Ali Bawafie; Muhammad Wahyuddin Abdullah; Abdul Wahid Haddade (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2024)
This research aims to analyze the development of a creative economy based on the tepo seliro synergy in halal tourism in Petekeyan Village, Jepara. A phenomenological approach was used, with data collected through in-depth interviews with key informants selected via purposive sampling. The analysis focused on six indicators of creative economic development and their connection to the five values of tepo seliro, examining their role in the success of Petekeyan's halal tourism industry. The findings show that creative entrepreneurs in the region uphold the value of tepo seliro, including honesty, not engaging in illegal activities, offering equal job opportunities, helping others, and ensuring security. The synergy of tepo seliro has contributed to the success of halal tourism by fostering a welcoming, safe, and respectful environment for all visitors